Achieving pain control in early rheumatoid arthritis with baricitinib monotherapy or in combination with methotrexate versus methotrexate monotherapy. Issue 1 (9th March 2022) - Taylor, Peter C.; Alten, Rieke; Álvaro Gracia, Jose María; Kaneko, Yuko; Walls, Chad; Quebe, Amanda; Jia, Bochao; Bello, Natalia; Terres, Jorge Ross; Fleischmann, Roy
Abstract : Objectives: This post hoc analysis assessed speed, magnitude and maintenance of pain improvement in patients with early rheumatoid arthritis (RA) receiving baricitinib, baricitinib and methotrexate (MTX), or MTX over 1 year. Cumulative pain and quality of life benefits were also assessed. Methods: Randomised, double-blind, phase 3 study RA-BEGIN (NCT01711359 ) compared baricitinib 4 mg (N=159), baricitinib 4 mg +MTX (N=215) and MTX (N=210) in patients with RA who had no or limited prior disease-modifying antirheumatic drug treatment. Pain was assessed on a 0–100 mm Visual Analogue Scale (VAS). Proportion of patients with ≥30%, ≥50% and ≥70% pain improvement from baseline; ≤20 mm and ≤10 mm on the pain VAS; and time to achieve pain improvement thresholds were assessed over 52 weeks, as were Patient Global Assessment (PtGA) and 36-Item Short Form Health Survey Physical Component Score (SF-36 PCS) outcomes. Results: Baricitinib monotherapy or combination with MTX provides greater (least square mean changes (LSM) from baseline −40 mm and −43 mm, respectively) and more rapid (median 12 and 8 weeks to ≥70% improvement, respectively) pain relief than MTX alone (LSM −31 mm, median 20 weeks to ≥70% improvement) over 52 weeks. Baricitinib, alone or combination, provides 9–10 additional weeks of limited to no pain, similar gain in achievable wellness measured through PtGA, and 5–7 additional weeks with change in SF-36 PCS ≥5 vs MTX over 1 year. Conclusions: Patients treated with baricitinib reported significantly greater and more rapid pain relief, more weeks with limited to no pain, and clinically meaningful improvements in physical health than patients treated with MTX alone over 1 year.